2018
DOI: 10.1007/s11739-018-1821-2
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive auto-titrating ventilation (AVAPS-AE) versus average volume-assured pressure support (AVAPS) ventilation in hypercapnic respiratory failure patients

Abstract: Auto-titrating noninvasive ventilation (NIV) has been developed as a new mode applying variable expiratory-positive airway pressure (EPAP) in addition to variable inspiratory pressures (IPAP), both to deliver targeted tidal volume (VT) and to eliminate upper airway resistance. The purpose of this study is to evaluate whether NIV with auto-titrating mode will decrease more PaCO within a shorter time compared to volume-assured mode in hypercapnic intensive care unit (ICU) patients. The hypercapnic respiratory fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
6
0
2
Order By: Relevance
“…Actually, target tidal volume of the two groups was set similarly 6-8 ml/ideal kg of the patient; but, the actual tidal volume was significantly higher in auto titrating group. Our findings were supported with several studies [11,12]. This might be explained by better elimination of upper airway resistance and improved lung mechanics.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Actually, target tidal volume of the two groups was set similarly 6-8 ml/ideal kg of the patient; but, the actual tidal volume was significantly higher in auto titrating group. Our findings were supported with several studies [11,12]. This might be explained by better elimination of upper airway resistance and improved lung mechanics.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our results, Gursel et al investigate the efficiency of AVAPS-AE mode in hypercapnic respiratory failure. The authors found 10 mmHg reduction in PaCO2 levels had been achieved within a short time period in autotitrating group [11].The more efficient PaCO2 reduction in Auto titrating mode may be attributed to the higher tidal volume that was achieved. Recently, two further studies reported that this ventilation mode effective and safe in patients with chronic obstructive pulmonary disease (COPD) and hypercapnic respiratory failure [12,13].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…81 In a retrospective, cohort-matched trial, Gursel et al evaluated the addition of AutoEPAP to Va-BPAP in a heterogeneous group of hypercapnic patients admitted to ICU. 82 The target tidal volume set for both groups was similar (501 AE 42 mL for Va-BPAP-AutoEPAP vs 497 AE 37 mL for Va-BPAP). A significant difference in the reduction in PaCO 2 in the first 6 h was seen favouring Va-BPAP-AutoEPAP (7 AE 7 vs 2 AE 5 mm Hg), with PaCO 2 falling greater than 5 mm Hg in 93% of those with added AutoEPAP compared to 60% of those using volume assurance alone.…”
Section: Figurementioning
confidence: 96%
“…In a retrospective, cohort‐matched trial, Gursel et al . evaluated the addition of AutoEPAP to Va‐BPAP in a heterogeneous group of hypercapnic patients admitted to ICU . The target tidal volume set for both groups was similar (501 ± 42 mL for Va‐BPAP‐AutoEPAP vs 497 ± 37 mL for Va‐BPAP).…”
Section: Volume‐assured Pressure Supportmentioning
confidence: 99%